A dynamic perspective of trust in virtual teams: the role of task, technology and time. (2008) - Araujo, Andre L.; Chidambaram, Laku
The virtual environment differs remarkably from organisational contexts where people meet at the same place and at the same time. Scholars have argued that what makes it possible for teams to effectively function in this lean environment is trust. Surprisingly, while the understanding of trust is gaining importance in the IS literature, little effort has been made to understand the effects of context on trust development in virtual teams. Drawing upon Time Interaction Performance (TIP) theory, this paper develops a theoretical model (referred to as the v-TIP model) along with a set of propositions that address trust development in virtual teams by integrating three key constructs - trust, task and time. Specifically, the v-TIP model suggests that the context defined in terms of the technology and task type will be a strong predictor of trust, thus affecting the performance of virtual teams over time.